Ultrasonic Assisted Microwave Processing System for Optimized Production of Biodiesel from Coconut Oil - Jabar, Azyan Hazwani (2011)
Biodiesel, a liquid fuel derived from plant oils or animal fats, represents a renewable energy source. The purpose of this research is to improve the coconut biodiesel production process using microwave transesterification and ultrasonic assisted microwave transesterification. This system will identify the yield from the combined ultrasonic and microwave, in terms of its rapidity and efficiency to transesterified. Some of the problems faced when the biodiesel production currently done at 1 to 2 hour in industry, so the technique obtained in this study probably can solved the problem in case of time consuming. A process for the production of the methyl ester of coconut oil for use as a biodiesel fuel has been studied. The essential part of the process is the transesterification of the coconut oil with methanol, in the presence of a catalyst, to yield the methyl ester as a product and glycerine as a by-product. Experiments have been performed to determine the optimum conditions for the preparation of the coconut biodiesel. The optimum conditions were: (1) 1.0% sodium hydroxide catalyst (dissolved in methanol) based on weight of coconut oil and 100% excess of the stoichiometric amount of required anhydrous alcohol; (2) extremely vigorous agitation with 24 kHz ultrasonic frequency until the reaction mixture (oil and methoxide) becomes thoroughly mixed; (3) microwave irradiation of the mixture. Maximum yields of 95%, were obtained for coconut oil by microwave transesterification in 3 mins. Whereas the washing process only takes 7 mins for every cycle by using microwave method compared to 45 mins in conventional method. When the reaction was assisted with ultrasonic, the optimum yield is 97.20%, where the time taken for ultrasonic was about 5mins and microwave about 3min, which gives total time 8mins. This results extremely favorably to the hour of processing required by conventional methods. A factor that is highly important during microwave heating is dielectric properties of material. Dielectric properties of coconut oil, methanol, sodium hydroxide, mixture of methanol and catalyst and first mixture between coconut oil and methoxide were determined using an open-ended, connected to a network analyzer. The important part of this dielectric measurement is the microwave dielectric detection of transesterification process at frequency 2.45 GHz. Result of the measurement over the frequency range shows drastic changes on the dielectric properties in the first 3 minutes of the reaction and after 3 minutes, the dielectric properties slowly decreases and approaches to the dielectric properties of biodiesel and glycerin. This result gives valuable information on the optimum mixing time of transesterification reaction. These properties could also be used to estimate absorbed power by the mixture for the application in microwave transesterification process as dielectric loss of the mixture change from 20 to about 0.5 as the transesterification reaction complete.